2016
DOI: 10.1080/14330237.2016.1185912
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence among HIV positive pregnant women in South Africa

Abstract: The aim of the study was to determine the prevalence of intimate partner violence (IPV) and associated factors among pregnant HIV-infected women in primary health care facilities in Nkangala and Gert Sibande districts, Mpumalanga, South Africa. Participants were 673 women who were, on average, 28.39 ± 5.73 years old. Data were collected through Audio Computer Assisted Self Interview (ACASI), and analysed using the IBM Statistical Package for Social Sciences (SPSS). Overall, 56.3% reported having experienced ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 32 publications
5
43
2
Order By: Relevance
“…This is consistent with findings of previous studies that intimate partner violence is commonly perpetrated against WLWH [7577]. In a study in South Africa, WLWH who conceived without discussing their pregnancy intentions with their partners experienced more violence from their partners than WLWH who did discuss their pregnancy intentions [78].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with findings of previous studies that intimate partner violence is commonly perpetrated against WLWH [7577]. In a study in South Africa, WLWH who conceived without discussing their pregnancy intentions with their partners experienced more violence from their partners than WLWH who did discuss their pregnancy intentions [78].…”
Section: Discussionsupporting
confidence: 91%
“…Experiencing HIV-related stigma is not uncommon for MSM living with HIV/AIDS [22,23], and may play a role in IPV. Among pregnant women living with HIV in South Africa, for example, greater HIV-related stigma was associated with greater combined physical and psychological IPV [24], and women living with HIV reporting high HIVrelated stigma reported more frequent physical IPV, social isolation and helplessness [25]. Despite the large number of MSM in China, little is known about the IPV experience among those living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A WHO multi-country study on women's health and domestic violence against women found the prevalence of violence during pregnancy to vary from 1 to 28%, with many in the range of 4-12%. [11][12][13][14][15] These include injuries, impairment, postpartum depression, miscarriage, unsafe abortion, low birthweight, pre-term delivery, caesarean sections, and sexually transmitted infections. 4 Various population and facility-based studies in India have found a rate of violence against pregnant women of between 13 and 49%.…”
Section: Introductionmentioning
confidence: 99%
“…10 Several studies in high-and low/middle-income countries have reported adverse health outcomes of VDP. [11][12][13][14][15] These include injuries, impairment, postpartum depression, miscarriage, unsafe abortion, low birthweight, pre-term delivery, caesarean sections, and sexually transmitted infections. The limiting impact of violence on antenatal care seeking by women has been well documented.…”
Section: Introductionmentioning
confidence: 99%